2020
DOI: 10.1021/acs.jnatprod.9b01006
|View full text |Cite
|
Sign up to set email alerts
|

Constituents of Two Dioscorea Species That Potentiate Antibiotic Activity against MRSA

Abstract: The isolation of two diarylnonanoids from Dioscorea cotinifolia possessing antibiotic-potentiating activity against resistant strains of S. aureus are reported. The diarylnonanoids are a class of natural products similar in structure to the diarylheptanoids, which have a wide spectrum of reported biological activities. One of the diarylnonanoids (1) isolated possesses a chiral center and to deduce its configuration, the modified Mosher ester method was used. Using both 1D and 2D NMR data, as many protons as po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…The NorA inhibition by chalcones and other EPIs seems to be strongly influenced by the degree of hydrophobicity, lipophilicity [144], and methylation [144], and methoxy group [145]. The crucial pharmacophores for NorA EPI are given as being a hydrogen bond acceptor, having a positive charge, presence of aromatic rings, and a hydrophobic region [146]. The EPI activity of terpenes such as eugenol and derivatives [146] showed that carvacrol and thymol modulation [147] could be due to competitive inhibition through hydrophobic lipophilic interactions and H bond formation.…”
Section: Inhibition Of Mfs Efflux Pumps Of S Aureus 71 Nora Norb and ...mentioning
confidence: 99%
See 1 more Smart Citation
“…The NorA inhibition by chalcones and other EPIs seems to be strongly influenced by the degree of hydrophobicity, lipophilicity [144], and methylation [144], and methoxy group [145]. The crucial pharmacophores for NorA EPI are given as being a hydrogen bond acceptor, having a positive charge, presence of aromatic rings, and a hydrophobic region [146]. The EPI activity of terpenes such as eugenol and derivatives [146] showed that carvacrol and thymol modulation [147] could be due to competitive inhibition through hydrophobic lipophilic interactions and H bond formation.…”
Section: Inhibition Of Mfs Efflux Pumps Of S Aureus 71 Nora Norb and ...mentioning
confidence: 99%
“…The crucial pharmacophores for NorA EPI are given as being a hydrogen bond acceptor, having a positive charge, presence of aromatic rings, and a hydrophobic region [146]. The EPI activity of terpenes such as eugenol and derivatives [146] showed that carvacrol and thymol modulation [147] could be due to competitive inhibition through hydrophobic lipophilic interactions and H bond formation. The α-bisabolol sesquiterpene from Matricaria chamomilla L reduced the norfloxacin MIC from 256 µg/mL to 32 µg/mL, although its mechanism of action is unclear.…”
Section: Inhibition Of Mfs Efflux Pumps Of S Aureus 71 Nora Norb and ...mentioning
confidence: 99%